Holocaust in Lithuania: Annihilation of the Jewish Communities of Palanga and Darbėnai Rural Areas of Kretinga County in Summer and Autumn 1941 - Rukšėnas , Alfredas (Genocidas ir rezistencija, 2015)
The article is dedicated to the annihilation of the Jewish communities of Palanga and Darbėnai rural areas of Kretinga County in summer and autumn 1941. The annihilation is considered to be the outcome of cooperation between the German military and civil administration, Tilsit operational squad and Lithuanian institutions (Lithuanian Security Police of Telšiai security district [Kretinga District], public police and subordinate auxiliary police). It has been established that 51 persons (public police officers and members of the auxiliary police squad) indirectly contributed to the genocide of Jews in Palanga rural area. Of these, 15 contributed directly, i.e. shot or otherwise executed victims. In Darbėnai rural area 33 persons (32 public police officers, members of the auxiliary police squad and one municipal official) indirectly contributed to the genocide of Jews. Of these, 13 contributed to the death of Jews directly, i.e. shot the victims. A total of 84 persons in these rural areas contributed indirectly to the genocide of Jews. Of these, 28 participated in the killings directly, i.e. shot the victims.
Keywords: german occupation; jews; Holocaust; Kretinga